Pulling Strings with Puppet Configuration Management Made Easy - TURNBULL, JAMES (FirstPress, 2012)
This book introduces the reader to Puppet––a Ruby-based configuration management and automation tool for Linux and Unix platforms. The book is a beginning-to-intermediate guide to Puppet. It is aimed at system administrators, operators, systems engineers, and anyone else who has to manage Linux and Unix hosts.